Vlogging White Privilege Abroad: Eat Your Kimchi's Eating and Spitting Out of the Korean Other on YouTube. (5th September 2017) - Oh, David C.; Oh, Chuyun
Abstract : Over several years, the YouTube channel Eat Your Kimchi, a White expatriate video log about South Korea, generated a sizeable audience. In the videos, Martina and Simon Stawski draw upon discourses that empower their identities as a privileged group of cultural outsiders—valued and othered for their White difference. To benefit from their global advantage, they essentialize differences between the West/themselves and Korea/ns in order to emphasize White and Western superiority. As a consequence, they reject hybridity by both mocking Korea/ns as an exotic other and by consuming it as an exotic delight. Their strategies reflect colonial‐era discourses seen in the travel logs of White "adventurers" that are transformed to the current social, global, and technological conjuncture.